One-person and collective executive bodies of local and regional government units - Stanisław Bułajewski (Journal of Modern Science)
Monocracy and collegiality of the executive bodies of local and regional government units have been the subject of doctrinal analysis for many years. Against this background, a number of positions have been developed that are often mutually exclusive. Some representatives of the doctrine argue that the district head and the marshal of a province are one-person bodies of local and regional government units, and some believe the opposite and state that these persons are not independent bodies of local and regional government units, but only (as provided by laws on the organization of local and regional government) the heads of executive bodies. There is also a view (it will be presented in the article) that the omission of the district head and marshal as executive bodies in the laws on the organization of local and regional government is a violation of the constitutional dichotomous structure, which does not provide for a third category of bodies. Accordingly, in the article (based on a number of views) I discussed not only the types of executive bodies and their basic powers in local and regional government units, but also listed the advantages and disadvantages associated with one-person or collective executive bodies in general.